Design and analysis of a novel quasi Z source based asymmetric multilevel inverter for PV applications - Deepa Sankar; C. A. Babu (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
A novel Quasi Z source (QZS) based Asymmetric Multilevel Inverter for Photovoltaic application is proposed in this paper. It consists of an Impedance source-based dc-dc converter and Asymmetric Multilevel Inverter (AMLI). QZS network can buck/boost the input DC voltage eliminating separate DC-DC boost converter. MLI topology with reduced switches and DC input provide high quality output with large levels. DC input magnitude of the inverter is based on an algorithm. The system ensures high voltage gain, low switching stress, lessened gate circuitry, high reliability and better harmonic profile. Low THD values ensures reduced filter size and hence cost. The theoretical concepts and parameter design of the proposed topology is illustrated in detail. The performance analysis is verified using Matlab/Simulink environment.